2009
DOI: 10.1097/tp.0b013e31819e02d4
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Photopheresis Efficiently Impairs the Proinflammatory Capacity of Human 6-Sulfo LacNAc Dendritic Cells

Abstract: These novel findings indicate that ECP efficiently impairs the proinflammatory capacity of slanDCs, which may represent an important mechanism for the therapeutic efficiency of ECP in GVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…We observed that neither aGVHD response nor aGVHD‐free survival were associated with cell doses even when the hematologic counts or apheresis yield were divided into quartiles, confirming literature reports . A possible explanation is given by studies showing how the cell type (the number of dendritic cells or the number of regulatory T cells generated) can affect the GVHD response; therefore, it appears evident that the biologic response is probably the key affecting the response, something this study indirectly confirms.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We observed that neither aGVHD response nor aGVHD‐free survival were associated with cell doses even when the hematologic counts or apheresis yield were divided into quartiles, confirming literature reports . A possible explanation is given by studies showing how the cell type (the number of dendritic cells or the number of regulatory T cells generated) can affect the GVHD response; therefore, it appears evident that the biologic response is probably the key affecting the response, something this study indirectly confirms.…”
Section: Discussionsupporting
confidence: 86%
“…The mechanism of action of ECP in GVHD is not fully understood. It has been proposed that ECP modulates host effector cells, including CD8+ T‐lymphocytes, natural killer cells, and circulating antigen‐presenting cells, leading to an attenuation of host antigen‐presenting activity and thus to the development of tolerance . In particular, an elegant study revealed that ECP induces a high percentage of processed monocytes to enter the antigen‐presenting dendritic cell (DC) differentiation pathway, within a single day, as determined by enhanced expression of over 1000 genes, independent of disease state, supporting the concept that, in the future, the ECP might represent a source of DC …”
Section: Discussionmentioning
confidence: 99%
“…Even before dying, human DC treated with 8-methoxypsoralen and UVA, promote Th2-biased responses and decrease drastically their ability to drive Th1 polarization [107, 108]. Once reinfused, the ECP-treated leukocytes are retained primarily in the spleen and liver [100, 101], likely by internalization by tissue-resident macrophages and immature DC, as shown for UV-B-irradiated splenocytes injected i.v.…”
Section: Role Of Apoptotic Cells In Extracorporeal Photopheresis In Tmentioning
confidence: 99%
“…However, slanDCs have been rarely considered a matter of interest in the allogeneic HSCT setting, in spite of their potential role in the pathogenesis of GVHD [for their induction of T helper type 1 (Th1) immune response and production of TNF‐α in response to LPS], GVL (for their ability to promote tumour cytotoxicity and NK cell activation) and in the first defence against infections during early post‐transplant (for their interaction with neutrophils and NK cells). In fact, to the best of our knowledge, only one study has previously evaluated the reconstitution of slanDCs in patients' PB (although limited to the first 100 days post‐allogeneic HSCT) , while only indirect evidence of the role played by circulating slanDCs in chronic GVHD (cGVHD) was available at the beginning of our study .…”
Section: Introductionmentioning
confidence: 99%